How to prepare and deliver a great talk - Martin, Seamus; Gemayel, Rita (My University, 2019)
Giving a talk can be daunting, particularly for scientists at the very early stages of their careers. Standing in front of an audience and speaking for 20–30 minutes do is never easy, and even those who do it for a liv- ing often confess to getting nervous before a talk. It is an oft-quoted fact that public speaking ranks higher than dying or jumping from a plane (with a parachute we hasten to add) on lists of ‘what people fear the most’. Anyone who has experienced the fear of public speaking knows very well just how stomach-churning the thought of an upcoming talk can be; the dread, the sleepless nights, the thought that nothing will come out when you open your mouth, or even worse, that you will speak complete gibberish. If you have felt this way before giving a talk, do not worry, you are not alone, we have all had these fears at some stage
PUBLISHED
Keywords: Public speaking; Speech writing; Scientific communication